A content-quality and optimization analysis of YouTube as a source of patient information for bipolar disorder - Jawza F. Alsabhan; Haya M. Almalag; Norah O. Abanmy; Yara I. Aljadeed; Reema H. Alhassan; Awatif B. Albaker (Elsevier, 2024)
Background: The goal of this study was to identify and evaluate the use of Arabic YouTube videos on BD as a resource for patient education. Methods: A cross-sectional evaluation of YouTube videos as a source of information for patients with BD in Arabic was performed. The study was observational and, because it did not involve human subjects, it followed the STROBE guidelines whenever possible. The quality of the videos was assessed using the validated DISCERN instrument. The search strategy involved entering the term "bipolar disorder" in the YouTube search bar, and only YouTube videos in Arabic were included. Results: A total of 58 videos were included in this study after removing duplicates and videos unrelated to BD (Figure 1). The most common source of videos was others (38%), followed by physician (33%), educational (26%), and hospital (3%). Resources covering symptoms and prognosis were mostly in the "others" category (41%). The resources or videos that covered treatment options were mainly created by physicians (41%). However, resources or videos that included a personal story mainly belonged to the "others" category (67%). Conclusion: Visual health-related instructional resources still have a significant shortage. This study highlights the poor quality of videos about serious illnesses like BD. Evaluation and promotion of the creation of visual health-related educational resources should be the primary goal of future study.